Developing Variation in the Late Work of Morton Gould and Why It Matters - J. Wesley Flinn (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2021)
American composer Morton Gould (1913-1996) was remarkably consistent stylistically over the course of his compositional career; this project examines certain motivic transformational techniques used in two of his last works, Stringmusic (1993, winner of the Pulitzer Prize) and Remembrance Day (Soliloquy for a Passing Century) (1995). These techniques, which can generally be filed under the principle of developing variation, are: 1. Mirroring and reversal; 2. Rotation; 3. Motivic expansion and contraction; 4. Additive sets; and 5. Asymmetric injection. After an overview of each technique, I give a full analysis of the fourth movement of Stringmusic using the approaches described within the paper. Finally, to show the pedagogical possibilities, I connect the use of the various analytic techniques to the idea of corporate embodiment of analysis, taking the idea of music theory out of the classroom and onto the football field.
Keywords: Morton Gould; Developing Variation; Schoenberg; Pedagogy; Wind Band; Analysis